Application of three-dimensional-printed porous tantalum cones in total knee arthroplasty revision to reconstruct bone defects - Ao, Yunong; Guo, Lin; Chen, Hao; He, Rui; Yang, Pengfei; Fu, Dejie; Gu, Lingchuan; Peng, Yang; Xiong, Ran; Yang, Liu; Wang, Fuyou (Frontiers in Bioengineering and Biotechnology, 2022)
Purpose: Three-dimensional (3D) printing technology has emerged as a new treatment method due to its precision and personalization, this study is performed to explore the application of 3D-printed personalized porous tantalum cone for reconstructing the bone defect in total knee arthroplasty (TKA) revision. Methods: Between November 2017 and October 2020, six patients underwent bone reconstruction using 3D printed porous tantalum cone in TKA revision. The knee function was assessed with the Hospital for Special Surgery (HSS) score pre- and postoperatively. Pain was measured by the visual analogue scale (VAS) pre- and postoperatively. The quality of life was measured using 36-Item Short Form Health Survey (SF-36) pre- and postoperatively. were used to evaluate the relief of pain. Operation time, intraoperative blood loss, postoperative drainage volume and complications were also recorded in detail. At the last follow-up, all patients received X-ray and computed tomography to confirm the effect of bone reconstruction. Results: After an average follow-up duration of 26.3months, no patients developed any operation related complication. The average intraoperative blood loss and postoperative drainage volumes were 250.1±76.4ml and 506.7±300.8ml, respectively. At the last follow-up, the HSS score was significantly higher than that before operation, indicating that the knee function was significantly improved(p<0.001). During follow-up, the mean VAS score decreased and the mean SF-36 score increased, both of them were significantly improved compared with preoperative(p<0.001). The radiology examination at final follow-up showed that cones implanted into the joint were stable and bone defects were effectively reconstructed. Conclusion: This preliminary study demonstrates 3D-printed porous tantalum cone could effectively reconstruct bone defects and offer anatomical support in TKA revision. Further studies are still needed to be performed to confirm the long-term effect of 3D-printed tantalum cone for reconstructing bone defects.